Fabrication and characterization of PZT-PMnN-PSbN ceramics doped with ZnO - Tho, Nguyen Truong; Vuong, Le Dai (Hue University Journal of Science: Natural Science, 2020)
The effect of the ZnO addition to the pure perovskite PZT-PMnN-PSbN ceramics sintered at 950–1200 °C was investigated. The phase structure of ceramics changes from rhombohedral to tetragonal, and the sintering temperature decreases with the increase of the ZnO content. The limited Zn2+ concentration for its solubility in PZT–PMnN–PSbN systems is about 0.25% wt. At this concentration, the ceramic exhibits a density of 8.20 g/cm3 and dielectric constants of 1,555 for εr and 32,900 for εmax. The highest value of εmax (about 22,000) was found at 1 kHz at Tm around 575 K. The diffuse phase transition was determined by using the extended Curie-Weiss law. Cole-Cole analyses show the non-Debye-type relaxation in the system.